Human Resource Management at Mts Manbaul Ulum Tangsil Wetan Wonosari Bondowoso - Rahman, Nurur Rahman (Edukasiana: Journal of Islamic Education, 2024)
AbstractThis study explores the human resource management (HRM) practices at MTs Manbaul Ulum Tangsil Wetan Wonosari Bondowoso, aiming to understand recruitment, competency development, career advancement, performance evaluation, and compensation management within the madrasah context. With a qualitative approach, data were gathered through in-depth interviews, observations, and document analysis involving madrasah leaders, teachers, and staff. The thematic analysis method was used to identify relevant patterns. Findings reveal that HRM at MTs Manbaul Ulum encompasses a systematic recruitment and selection process to ensure the selection of qualified educators aligned with Islamic values. Competency development is enhanced through initial training, monthly internal programs, and external training sessions. Career advancement opportunities are structured into categories that provide clear growth pathways for educators. Regular performance evaluations, conducted quarterly, focus on both discipline and teaching effectiveness, with compensation adjustments made accordingly. Although compensation remains modest, a gradual increase is being implemented. These HRM strategies contribute significantly to improving educational quality in an Islamic educational institution. This research highlights the importance of structured HRM practices in supporting madrasah’s mission to deliver quality education while aligning with religious values.Keywords: human resource management, Islamic education, recruitment, competency development, performance evaluation